Serum adiponectin and its association with cardiometabolic variables in an adult population from Carhuamayo (Junín-Perú) - Carranza1, Elizabeth (2013)
The objective of this study was to determine the association between serum adiponectin levels and cardiometabolic risk factors in a high altitude population. We included 88 adults (31 men and 57 women), natives from Carhuamayo, town at 4146 m. Anthropometric data were recorded and blood pressure was measured. Serum levels of lipidic profile, glucose and adiponectin were determined. Mean values of serum adiponectin in women were found to be significantly higher than those in men. Estimated hipoadiponectinemia (<4 μg/mL) was 23,9% in the total sample, 45,2% in men and 12,4% in women; the serum adiponectin highest prevalence (47,6%) corresponded to the hipoadiponectinemic group. Serum adiponectin level showed significantly negative correlation with BMI and with serum triglyceride concentration, and was positively and significantly correlated with HDL-cholesterol. Was concluded that hipoadiponectinemia is highly associated with metabolic syndrome and with hypertriglyceridemia, which is the most prevalent component of metabolic syndrome in the population studied.